Implementasi Algoritma Multiplicative Random Number Generator Dalam Game Adventure Pandai To Be Berbasis Android - Ardiansyah Yudistira Putra, Rocky; Mashuri, Chamdan (Inovate, 2023)
Game-based learning is a learning model that is often applied to students so that students can learn while playing games. In this research, the learning model especially the learning To Be in English is applied to help Madrasah Ibtidaiyah students compose sentences connecting the subject and predicate in English. Game-based learning are applied with the adventure game genre to be used for interesting learning model and make students more diligent and concentrate in completing the existing tasks, so that it is expected to increase students' interest and motivation to learn. This research uses a Multiplicative Random Number Generator in randomizing the questions in the game in order to produce different questions between users by using five different types of parameters. The result of this research is the Pandai To Be Adventure Game with Android-based. The application of the Multiplicative Random Number Generator algorithm in the game can run well. This is evidenced by the game's success in randomizing the questions that arise every time it is played. Even though the question bank is sequential, when the Pandai To Be Adventure Game is played, it will display a variety of question displays. Keywords: Adventure Game, Learning To Be, Multiplicative Random Number Generator.